Utility of radiation in the prevention of heterotopic ossification following total hip replacement and traumatic acetabular fracture - Reszke, Joanna; Zarzycka, Małgorzata; Makarewicz, Roman; Windorbska, Wiesława (Contemporary Oncology/Współczesna Onkologia, 2001)
Heterotopic ossification (HO) is defined as the formation of mature lamellar bone in nonosseous tissues. The most common cause is trauma but others include neurogenic causes and myositis ossificans. Heterotopic ossification is the most common problem following total hip replacement (THR) and surgical repair of traumatic acetabular fracture (TAF). When formed in the paraarticular tissues it may cause significant symptoms, such as pain impaired joint mobility or complete ankylosis of the joint. Without receving any kind of prophylaxis the incidence of HO is about 30-80%. Predisposing high risk factors for heterotopic ossification are severe hip trauma, previous development of heterotopic ossification, hypertrophic osteoarthritis, active rheumatoid spondylathritis and male sex. Several etiologic theories exist regarding the formation of HO following open reduction and internal fixation; however, most concur that pluripotent mesenchymal cells differentiate into osteogenic precursor cells as a result of combination of the traumatic setting of the fracture and the surgical manipulation. The incidence of HO is known to be lovered by radiation therapy and it is thought that the radiation acts in some way to impede the proliferation of pluripotential mesenchymal cells that could differentiate into osteoblastic stem cells. This incidence is also known to be lowered by the use of nonsteroidal anti-inflammatory drugs, most particulary indomethacin; however, compliance is questionable and approximately 37% of patiens do not complete therapy secondary to side effects. Since the initial report by Coventry and Scanlon many reports documenting the efficacy of radiotherapy as a prophylactis measure have appeared. There has been an evolution in technique and doses in the past 20 years. Previous studies have compared the use of a single fraction of radiation (typically 6-8Gy) with multiple fractionation schemes, e.g. 20 Gy in 10 fractions, 10 Gy in 5 fractions, and determined that single fractionation scheme is equally effective. Preoperative radiotherapy of the operative site applied within 4 h prior to elective hip surgery and total hip arthroplasty appears to be equally effective to currently accepted postoperative radiotherapy regimens in prevention of clinically significant heterotopic ossification about the hip.